Mussel inspired functionalization of carbon nanotubes for heavy metal ion removal1. Issue 84 (16th September 2015) - Xie, Yili; Huang, Qiang; Liu, Meiying; Wang, Ke; Wan, Qing; Deng, Fengjie; Lu, Long; Zhang, Xiaoyong; Wei, Yen
<x xml:space="preserve">Abstract</x> Polyethylenimine functionalized carbon nanotubes were prepared through mussel inspired chemistry and the Michael addition reaction, and utilized for the adsorption of Cu2+ from water.